Health Data Integration with Secured Record Linkage and Trust-Level Security Based Authentication - Katiwal, Varsha; Balani, Nisha; Dudhe, Priyanka (International Journal of Computer Sciences and Engineering, 2025)
Discovering Knowledge from various health data domains requires the incorporation of healthcare data from diversified sources. Maintaining record linkage during the integration of medical data is an important research issue. Researchers have given different solutions to this problem that are applicable for developed countries where electronic health record of patients are maintained with identifiers like social security number (SSN), universal patient identifier (UPI), health insurance number, etc. These solutions cannot be used correctly for record linkage of health data of developing countries because of missing data, ambiguity in patient identification, and high amount of noise in patient information. We have proposed a privacy preserved secured record linkage architecture that can support constrained health data of developing countries such as Bangladesh. Our technique can unidentified identifiable private data of the patients while maintaining record linkage in integrated health repositories to facilitate knowledge discovery process. This concept motivates us to create a trust level security authentication. It means, this healthcare database will be fully secured using cryptography algorithm of encryption and decryption using AES algorithm and authentication will be controlled on “Trust Level Security”. It means that if any researcher or organization need to access this data, then he/she must have at least above average trust level. We score 1 as minimum trust level 10 as maximum trust level and 5 as an average trust level. Trust level will be calculated on the basis of how much other organizations and researchers trust on A researcher or organization.